Authentic Leadership and Knowledge-Sabotaging Behavior: A Test of Self-Determination Theory - Dewi; Adi Rahmat; Muhammad Rasyid Abdillah (Yayasan Education Al Aqsho Modern, 2023)
This study aims to see how the mediation of controlled motivation to share knowledge on the effect of authentic leadership on knowledge sabotage (study at one of the HTI companies in Riau). In addition, this study will also look at the interaction of the two variables. The type of research is explanatory research. The population is 198 people. Data analysis in this study uses SEM-PLS. Based on data processing, it was found that authentic leadership has a negative effect on knowledge-sabotage behavior, controlled motivation to share knowledge has a negative effect on knowledge-sabotage behavior, and controlled motivation to share knowledge mediates the influence of authentic leadership on knowledge-sabotage behavior. Specifically, the findings in this study indicate that authentic leadership indirectly plays an important role in reducing and preventing subordinates from engaging in counterproductive behavior such as knowledge-sabotage behavior. Controlled motivation is found to function as a mediation mechanism that explains the effect of authentic leadership on knowledge-sabotage behavior. Findings of this research offers a valuable contribution to broaden understanding of the mechanisms underlying authentic leadership to knowledge sabotage behavior.